Accuracy of the ELITe MGB assays for the detection of carbapenemases, CTX-M, Staphylococcus aureus and mecA/C genes directly from respiratory samples. Issue 2 (June 2020) - Boattini, M.; Bianco, G.; Iannaccone, M.; Charrier, L.; Almeida, A.; De Intinis, G.; Cavallo, R.; Costa, C.
Summary: Introduction: Bacterial lower respiratory tract infections (BLRTI) may represent serious clinical conditions which can lead to respiratory failure, intensive care unit admission and high hospital costs. The detection of carbapenemase- and extended-spectrum β-lactamase (ESBL)-producing Enterobacterales, as well as meticillin-resistant Staphylococcus aureus (MRSA), has become a major issue, especially in healthcare-associated infections. This study aimed to determine whether molecular assays could detect genes encoding carbapenemases, ESBL and MRSA directly from respiratory samples in order to expedite appropriate therapy and infection control for patients with BLRTI. Methods: The carbapenem-resistant enterobacterales (CRE), ESBL and MRSA/SA ELITe MGB assays were performed directly on 354 respiratory specimens sampled from 318 patients admitted with BLRTI. Molecular results were compared with routine culture-based diagnostics results. Results: Positive (PPV) and negative (NPV) predictive values of the CRE ELITe MGB kit were 75.9% [95% confidence interval (CI) 60.3–86.7] and 100%, respectively. PPV and NPV of the ESBL ELITe MGB kit were 80.8% (95% CI 63.6–91.0) and 99.1% (95% CI 96.6–99.8), respectively. PPV and NPV of the MRSA/SA ELITe MGB kit were 91.7% (95% CI 73.7–97.7)/100% and 98.3% (95% CI 89.8–99.3)/96.8% (95% CI 81.6–99.5), respectively. Discussion: Validity assessment of molecular assays detecting the main antibiotic resistance genes directly from respiratory samples showed high accuracy compared with culture-based results. Molecular assays detecting the main carbapenemase, ESBL, S. aureus and meticillin resistance encoding genes provide an interesting tool with potential to expedite optimization of antibiotic therapy and infection control practices in patients with BLRTI.